2012
DOI: 10.1111/j.1755-3768.2010.01956.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular motor function in relation to gross motor function in congenital and childhood myotonic dystrophy type 1

Abstract: Abnormalities of ocular motor function are frequently present. CTG repeat size correlates positively with altered versions/ductions and eyelid pathology. Gross motor dysfunction correlates with strabismus and defect versions/ductions, and eyelid pathology indicates involvement of myotonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
6
0
8
Order By: Relevance
“…These results confirm previous hypotheses of authors who suspected visual–spatial dysfunction based on (1) Wechsler Intelligence Scale for Children profile (very low scores on Object Assembly and Block Design 12,41,42 ) and (2) specific reading and spelling impairments in patients with childhood DM1 and no intellectual disability (no phonological deficit, severe impairment in searching for information in a television programme) 13 . These results are also in line with recent studies that reported a high rate (82%) of ocular motor abnormalities (alliterated conjugate eye movements), as well as visual function pathologies (low visual acuity, hyperopia, or astigmatism) in childhood DM1 43,44 . All these abnormalities could affect the development of the visual system and the ability to learn to read.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results confirm previous hypotheses of authors who suspected visual–spatial dysfunction based on (1) Wechsler Intelligence Scale for Children profile (very low scores on Object Assembly and Block Design 12,41,42 ) and (2) specific reading and spelling impairments in patients with childhood DM1 and no intellectual disability (no phonological deficit, severe impairment in searching for information in a television programme) 13 . These results are also in line with recent studies that reported a high rate (82%) of ocular motor abnormalities (alliterated conjugate eye movements), as well as visual function pathologies (low visual acuity, hyperopia, or astigmatism) in childhood DM1 43,44 . All these abnormalities could affect the development of the visual system and the ability to learn to read.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the disorder called sluggish cognitive tempo should be investigated with appropriate instruments in further research, 11 as well as hearing attention, given the abnormalities in visual development. 44 The low rate of somnolence (present in only four patients) contradicts the hypothesis of continuity between somnolence and attention deficit. The rate of excessive daytime sleepiness is lower than the rates observed in adults (nearly 30%) according to Yu et al 45 Our results should be understood in the context of the following study limitations.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…It was significantly correlated with poor motor performance expressed by MFM-P scores, which suggests it is a manifestation that evolves along disease course. Aring et al 17 documented swollen eyelids 'pseudoptosis' in their patients younger than 18 years, while blepharoptosis was reported to be rare.…”
Section: Discussionmentioning
confidence: 99%